2023
DOI: 10.3389/fpsyg.2023.1225698
|View full text |Cite
|
Sign up to set email alerts
|

Emotional control and factors differentiating it in the adult population of Poland during the COVID-19 pandemic

Abstract: IntroductionThe public health crisis related to the COVID-19 pandemic has had a negative impact on the mental health of both individuals and entire populations. The source of stress was not only the fear of getting sick, but also the restrictions introduced, such as: mass lockdown, the need to maintain social distance, quarantine or the mandatory use of personal protective equipment. Their introduction and maintenance caused various emotional reactions which often resulted in undesirable behavior leading to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Future studies should be interested in determining the factors underlying stress and anxiety, which may include social isolation, economic concerns, fear of dying, or of the unknown, etc. [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Future studies should be interested in determining the factors underlying stress and anxiety, which may include social isolation, economic concerns, fear of dying, or of the unknown, etc. [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…5 For example, the abrupt work setting transition during the pandemic made it difficult for Polish adults to balance remote work and housework, which in turn led to challenges in anger management. 6 During the pandemic, much of the US workforce transitioned to WFH. The 2021 Business Response Survey on the Coronavirus Pandemic reported that 31% of establishments increased employees' WFH opportunities by late 2020.…”
Section: Introductionmentioning
confidence: 99%
“…WFH during the pandemic has led to decreases in mental health (e.g., depression) and overall healthy behaviors in workers, manifesting as reduced physical activity 4 and unhealthy eating habits 5 . For example, the abrupt work setting transition during the pandemic made it difficult for Polish adults to balance remote work and housework, which in turn led to challenges in anger management 6 …”
Section: Introductionmentioning
confidence: 99%